Hotel’s Marketing On Instagram : Social Influence And Attitude Toward Instagram & Hotel Brand On Hotel Booking Intention And E-Wom - Yosua Parhorasan Manullang (Jurnal Minfo Polgan, 2024)
Instagram, a popular global mobile photo and video sharing platform with variety of features has become an important marketing tools especially for hotel. These paper aim to examine the consumer behavior model toward marketing on Instagram including factors and impact.This study express integrated model between marketing and social psychology theories through Instagram Hotel. Data have been collected via a structural online survey which respondent expected to visit the live Instagram Hotel then fill out the survey. Structural equation model (SEM) has been used to test the model. Compliance as a part of social psychology hasn’t strong affected for attitude toward Instagram rather than Identification and Internalization. On the other side, Hotel Booking Intention and Intention of e-WOM is impact from marketing. This study provided guidelines for hotel marketers to create marketing strategy through Instagram with considering how to create value for customer rather than impress customer with giving reward. Intention to purchase and e-WOM are impact of marketing definitely, however it would be starting with strategic approach that is by creating interactive ways (attractive photos and videos) by utilizing variety of Instagram features.The major limitation of this study is sample collection process due to on boundary of sample criteria to get strong point for analysis.